2021
DOI: 10.1016/j.metop.2020.100071
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic, antidyslipidemic and antioxydant effects of Vitellaria paradoxa barks extract on high-fat diet and streptozotocin-induced type 2 diabetes rats

Abstract: Backgroud Vitellaria paradoxa is a plant belonging to the Sapotaceae family and used in traditional medicine in the treatment of diabetes mellitus. The aim of this work was to evaluate the hypoglycemic, antidyslipidemic and antioxidant effects of V. paradoxa on type 2 diabetic rats. Methods To induce type 2 diabetes mellitus (T2DM), animals were fed a high-fat diet for 4 weeks followed by an intraperitoneal injection of 35 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(11 reference statements)
2
6
0
Order By: Relevance
“…We did observe the reduced blood glucose in creatine-supplemented diabetic animals (DCr group). However, we also observed polydipsia, polyphagia, and decreased body weight in STZ-induced diabetic animals, similar to previous reports [ 90 , 91 , 92 , 93 , 94 ]. Therefore, creatine supplementation in diabetic animals neither attenuated nor aggravated these clinical effects.…”
Section: Discussionsupporting
confidence: 92%
“…We did observe the reduced blood glucose in creatine-supplemented diabetic animals (DCr group). However, we also observed polydipsia, polyphagia, and decreased body weight in STZ-induced diabetic animals, similar to previous reports [ 90 , 91 , 92 , 93 , 94 ]. Therefore, creatine supplementation in diabetic animals neither attenuated nor aggravated these clinical effects.…”
Section: Discussionsupporting
confidence: 92%
“…However, a decrease in TC, TG, LDL-c, AI, and CRI and an increase in HDL-c and CI were shown in the groups treated with AEFV (110, 220, and 440 mg/kg). The work of Miaffo et al [ 46 ] also showed a decrease in the concentration of TC, TG, and LDL-c and a significant increase in the concentration of HDL-c following administration of the aqueous extract of the bark of Vitellaria paradoxa in rats subjected to HFD for 28 days. The hypocholesterolemic effect could be due to the ability of AEFV to inhibit cholesterol biosynthesis in the liver, decreased intestinal absorption of cholesterol, increased LDL receptors, and LDL uptake [ 47 ].…”
Section: Discussionmentioning
confidence: 98%
“…These noteworthy discoveries were concurred with an earlier study on the same plant, which established the plant's efficacy in preventing hypertriglyceridaemia and hypercholesterolaemia. Corroborating its efficacy in averting known treats of diabetes mellitus-related cardiac complications [ 21 , 61 ]. Flavonoids [ 48 ] and anthraquinones [ 62 ] detected in G. lotoides have been attributed to blood TG, TC, LDL-c, and VLDL-c reduction.…”
Section: Discussionmentioning
confidence: 99%